The Effect of Techno-Stress on Labour Management Relations - Salman, Abdulrasaq; Jimoh, Adams Lukman; Olawale, Yunusa Alabi (Journal of Techno-Social, 2025)
The rapid infusion of technology into the workplace has created a paradox in human resource management practice. As a result, there is a growing need to explore how techno-stress influences these relationships. The objective of this study is to determine the effect of techno-stress on labor-management relations. The study used a cross-sectional survey design. The target population comprised 319 employees of the Kwara State Internal Revenue Service (KW-IRS).  A sample size of 178 samples was determined via Krejcie and Morgan's sample size formula while random sampling technique was used. The finding reveals that techno-stress significantly undermines labour–management relations, which positively influence organizational performance, while techno-stress shows no significant effect on employees’ work–life balance. The study concluded that techno-stress can lead to psychological and physical strain. It is then recommended that organizations should encourage a healthy work-life balance and introduce stress management programs and resources.